Successful management of placenta percreta by cesarean hysterectomy with transverse uterine fundal incision - Matsuzaki, Shinya; Yoshino, Kiyoshi; Kajimoto, Etsuko; Tanaka, Yusuke; Mimura, Kazuya; Kanagawa, Takeshi; Kimura, Tadashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Placenta accreta presents one of the highest risks to pregnancy, and its more severe variant, placenta percreta, is particularly risky. The incidence of both conditions is increasing. Placenta percreta requires a cesarean hysterectomy for management, but the challenges associated with this surgery often result in severe obstetric hemorrhaging and high rates of maternal morbidity. Several recent obstetric studies have reported on the usefulness of the transverse uterine fundal incision for the management of placenta accreta and its variants. However, these reports included only a few cases of placenta percreta. Here we present a case of placenta percreta covering the anterior uterine wall that was successfully managed using a transverse fundal incision, which avoided incising the placenta at delivery and thus reduced maternal blood loss. After delivery, the patient underwent a total abdominal hysterectomy without the need for a blood transfusion. We conclude that a transverse uterine fundal incision can be very useful for the management of placenta percreta of the anterior uterine wall.